Budgetary impact from multiple perspectives of sustained antitobacco national media campaigns to reduce the harms of cigarette smoking. Issue 3 (27th April 2020) - Maciosek, Michael V; Armour, Brian S; Babb, Stephen D; Dehmer, Steven P; Grossman, Elizabeth S; Homa, David M; LaFrance, Amy B; Rodes, Robert; Wang, Xu; Xu, Zack; Yang, Zhuo; Roy, Kakoli
Abstract : Background: High-intensity antitobacco media campaigns are a proven strategy to reduce the harms of cigarette smoking. While buy-in from multiple stakeholders is needed to launch meaningful health policy, the budgetary impact of sustained media campaigns from multiple payer perspectives is unknown. Methods: We estimated the budgetary impact and time to breakeven from societal, all-payer, Medicare, Medicaid and private insurer perspectives of national antitobacco media campaigns in the USA. Campaigns of 1, 5 and 10 years of durations were assessed in a microsimulation model to estimate the 10 and 20-year health and budgetary impact. Simulation model inputs were obtained from literature and both pubic use and proprietary data sets. Results: The microsimulation predicts that a 10-year national smoking cessation campaign would produce net savings of $10.4, $5.1, $1.4, $3.6 and $0.2 billion from the societal, all-payer, Medicare, Medicaid and private insurer perspectives, respectively. National antitobacco media campaigns of 1, 5 and 10-year durations could produce net savings for Medicaid and Medicare within 2 years, and for private insurers within 6–9 years. A 10-year campaign would reduce adult cigarette smoking prevalence by 1.2 percentage points, prevent 23 500 smoking-attributable deaths over the first 10 years. In sensitivity analysis, media campaign costs would be offset by reductions in medical care spending of smoking among all payers combined within 6 years in all tested scenarios. Conclusions: 1, 5 and 10-year antitobacco media campaigns all yield net savings within 10 years from all perspectives. Multiyear campaigns yield substantially higher savings than a 1-year campaign.